2009
DOI: 10.1186/1477-7517-6-37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filtration on morphine and particle content of injections prepared from slow-release oral morphine tablets

Abstract: BackgroundInjections of mixtures prepared from crushed tablets contain insoluble particles which can cause embolisms and other complications. Although many particles can be removed by filtration, many injecting drug users do not filter due to availability, cost or performance of filters, and also due to concerns that some of the dose will be lost.MethodsInjection solutions were prepared from slow-release morphine tablets (MS Contin®) replicating methods used by injecting drug users. Contaminating particles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 14 publications
1
41
0
Order By: Relevance
“…Several studies [13,14] have evaluated the efficacy of IDUSF or wheel filters. Scott's research [13] also included some questions on filter preference.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies [13,14] have evaluated the efficacy of IDUSF or wheel filters. Scott's research [13] also included some questions on filter preference.…”
Section: Resultsmentioning
confidence: 99%
“…The bacteriological study in the present work highlighted the value of using filters with a porosity of less than 0.5 μm, as they limit the risk of bacterial and fungal infection to the largest extent possible. Although our study did not focus on particle analysis, we can comfortably affirm that particles are filtered more effectively by the lower porosity 0.22 and 0.45‐μm wheel filters than by Sterifilt .…”
Section: Discussionmentioning
confidence: 54%
“…The efficiency of the wheel filter in terms of particle filtration has been repeatedly shown in the literature for different wheel filter diameters as follows: 0.5 μm [28], 0.2 μm [1], 0.22 μm [24] and 0.22 and 0.45 μm [23]. With regard to bacteria filtration, a recent study showed that 0.22-μm wheel filters were effective in eliminating the strains tested (S. aureus, Streptococcus pyogenes and P. aeruginosa).…”
Section: Discussionmentioning
confidence: 96%
“…The objectives of the structured education were to: (i) provide instruction on wheel‐filtration based on recommended practice and current evidence ; (ii) increase knowledge of the advantages of wheel‐filtration; and (iii) promote uptake of the practice. The key steps of the structured education were: MSIC Health Education Officers (HEO) received refresher training in the method to ensure consistent delivery. Participants agreed to: (i) provide their own opioid tablet; (ii) follow instruction from the HEO; and, (iii) accept responsibility for any actual or perceived drug loss. The education session took place during normal operating hours in the injecting room (a room with eight open booths that can seat two people). The HEO explained what equipment was required (Table ) and collected it with the participant. The HEO sat beside the participant in the booth.…”
Section: Methodsmentioning
confidence: 99%
“…The objectives of the structured education were to: (i) provide instruction on wheel-filtration based on recommended practice [11] and current evidence [5]; (ii) increase knowledge of the advantages of wheelfiltration; and (iii) promote uptake of the practice. The key steps of the structured education were:…”
Section: Structured Educationmentioning
confidence: 99%